Horizontally Self‐Standing Growth of Bi2O2Se Achieving Optimal Optoelectric Properties. Issue 8 (8th June 2022) - Zou, Xiaobin; Sun, Yong; Wang, Chengxin
Abstract: Air‐stable 2D Bi2 O2 Se material with high carrier mobility appears as a promising semiconductor platform for future micro/nanoelectronics and optoelectronics. Like most 2D materials, Bi2 O2 Se 2D nanostructures normally form on atomically flat mica substrates, in which undesirable defects and structural damage from the subsequent transfer process will largely degrade their photoelectronic performance. Here, a new synthesis route involving successive kinetic and thermodynamic processes is proposed to achieve horizontally self‐standing Bi2 O2 Se nanostructures on SiO2 /Si substrates. Fewer defects and avoidance of transfer procedure involving corrosive solvents ensure the integrity of the intrinsic lattice and band structures in Bi2 O2 Se nanostructures. In contrast to flat structures grown on mica, it displays reduced dark current and improved photoresponse performance (on–off ratio, photoresponsivity, response time, and detectivity). These results indicate a new potential in high‐quality 2D electronic nanostructures with optimal optoelectronic functionality. Abstract : A new synthesis method is proposed to achieve horizontally self‐standing Bi2 O2 Se nanoplates on SiO2 /Si substrates by abrupt adjustment of the growing pressure during the growth. In contrast to flat Bi2 O2 Se nanoplates grown on mica, they display improved photoresponse performance, indicating a new potential in high‐quality 2D electronic nanostructures with optimal optoelectronic functionality.